"For Some Reason I Find it Hard to Work Quickly": Introduction to the Special Issue on Sluggish Cognitive Tempo. (June 2017) - Becker, Stephen P.
The body of research investigating the sluggish cognitive tempo (SCT) construct continues to accumulate at a rapid pace. This article provides an introduction to the Special Issue on SCT, which includes 10 empirical studies that collectively make a major contribution to the SCT knowledge base. Notably, the studies in this Special Issue include participants spanning in age from 4 to 64 years and from four continents, helping to move the field toward a life span, transcultural understanding of SCT. Together, these studies demonstrate that SCT symptoms can be distinguished from ADHD symptoms as early as preschool and that SCT does not fall under the overarching umbrella of ADHD. These studies also show SCT to be associated with a range of external correlates including internalizing symptoms, learning difficulties, functional impairment, and daily life executive functioning (but not performance-based measures of executive functions). Preliminary findings of SCT in relation to thyroid functioning and tobacco exposure are reported. In addition to providing a summary of the key themes across studies included in the Special Issue, this article highlights key ways in which future research can build from these studies. There is a particular need for research utilizing longitudinal, multi-method, and multi-informant designs that can shed light on the etiologies and developmental psychopathology of SCT across the life span.